Bad Phages in Good Bacteria: Role of the Mysterious orf63 of λ and Shiga Toxin-Converting Φ24B Bacteriophages - Dydecka, Aleksandra; Bloch, Sylwia; Rizvi, Ali; Perez, Shaili; Nejman-Falenczyk, Bozena; Topka, Gracja; Gasior, Tomasz; Necel, Agnieszka; Wegrzyn, Grzegorz; Donaldson, Logan W.; Wegrzyn, Alicja (Frontiers in Microbiology, 2017)
Lambdoid bacteriophages form a group of viruses that shares a common schema of genome organization and lifecycle. Some of them can play crucial roles in creating the pathogenic profiles of Escherichia coli strains. For example, Shiga toxin-producing E. coli (STEC), acquired stx genes, encoding Shiga toxins, via lambdoid prophages (Stx phages). The results obtained so far present the evidence for the relation between the exo-xis region of the phage genome and lambdoid phage development, however molecular mechanisms of activities of the exo-xis genes’ products are still unknown. In view of this, we decided to determine the influence of the uncharacterized open reading frame orf63 of the exo-xis region on lambdoid phages development using recombinant prophages, λ and Stx phage Ф24B. We have demonstrated that orf63 codes for a folded protein, thus, it is a functional gene. NMR spectroscopy and analytical gel filtration were used to extend this observation further. From backbone chemical shifts, Orf63 is oligomeric in solution, likely a trimer and consistent with its small size (63 aa.), is comprised of two helices, likely intertwined to form the oligomer. We observed that the deletion of phage orf63 does not impair the intracellular lambdoid phage lytic development, however delays the time and decreases the efficiency of prophage induction and in consequence results in increased survival of E. coli during phage lytic development. Additionally, the deletion of phage orf63 negatively influences expression of the major phage genes and open reading frames from the exo-xis region during prophage induction with hydrogen peroxide. We conclude, that lambdoid phage orf63 may have specific functions in the regulation of lambdoid phages development, especially at the stage of the lysis vs. lysogenization decision. Besides, orf63 probably participates in the regulation of the level of expression of essential phage genes and open reading frames from the exo-xis region during prophage induction.